Clinically-probed mechanisms of action in Fragile-X syndrome fail to normalize translational EEG phenotypes in Fmr1 knockout mice - Janz, Philipp; Bainier, Marie; Marashli, Samuel; Gross, Simon; Redondo, Roger L. (Neuropharmacology, 2025)
Fragile X syndrome (FXS) is a neurodevelopmental disorder caused by Fragile X Messenger Ribonucleoprotein (FMRP) deficiency. Electroencephalogram (EEG) changes in FXS include alterations of oscillatory activity and responses to sensory stimuli, some of which have been back-translated into rodent models by knocking-out the Fragile X messenger ribonucleoprotein 1 gene (Fmr1-KO). However, the validity of these EEG phenotypes as objective biomarkers requires further investigation. Potential pharmacotherapies such as mGluR5 inhibitors (e.g. CTEP; 2-chloro-4-((2,5-dimethyl-1-(4-(trifluoromethoxy)phenyl)-1H-imidazole-4-yl)ethynyl)pyridine), GABABR agonists (e.g. arbaclofen) and δ-containing GABAAR agonists (e.g. gaboxadol) have not translated into clinical success despite rescuing many phenotypes in the Fmr1-KO model. Yet none of these treatments have been assessed on EEG phenotypes in the Fmr1-KO model. Therefore, we set out to discover new EEG phenotypes in Fmr1-KO mice, using “task-free” and auditory-evoked (AEPs) and visually-evoked potential (VEP) paradigms, and probe their modulation by CTEP, arbaclofen and gaboxadol, using within-subjects designs. First, we report Fmr1-KO-associated EEG abnormalities that closely resemble those observed in FXS, including elevated gamma-band power, reduced alpha/beta-band coherence, increased AEPs and delayed VEPs. Secondly, we found that pharmacological treatment, at best, only partially normalized EEG phenotypes. CTEP restored alpha/beta-band coherence and AEP amplitudes but failed to normalize gamma power and VEP latencies. Conversely, arbaclofen reduced gamma power but did not restore coherence or AEP amplitudes and further delayed VEPs. Gaboxadol did not normalize any EEG phenotypes. We conclude that these compounds have limited ability to normalize these EEG phenotypes. [Display omitted] •Fmr1-KO mouse EEG abnormalities resemble those reported in FXS patients.•Pharmacological treatment only partially normalized EEG phenotypes.•CTEP restored coherence and AEP, but not gamma power and VEP abnormalities.•Arbaclofen reduced gamma power but did not restore other key readouts.•Gaboxadol did not normalize any EEG phenotypes.